2018
DOI: 10.1080/17476348.2018.1473037
|View full text |Cite
|
Sign up to set email alerts
|

Indications and complications of rigid bronchoscopy

Abstract: Rigid bronchoscopy is an invaluable tool for the management of airway disorders and an essential skill for an interventional pulmonologist. Since its introduction in the late 19th century, it has remained an important technique for the management of central airway obstruction, foreign body aspiration and massive hemoptysis. Areas covered: This article will review the history, indications, contraindication, technique and complications of rigid bronchoscopy. We will also briefly discuss the methods of anesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 57 publications
1
58
0
2
Order By: Relevance
“…With the rapid development of IP, the application of FB is becoming more and more widespread [3]. Compared to RB [4], FB is relatively easy to operate. It plays an increasing important role in clinical [[5], [6], [7], [8], [9]].…”
Section: Resultsmentioning
confidence: 99%
“…With the rapid development of IP, the application of FB is becoming more and more widespread [3]. Compared to RB [4], FB is relatively easy to operate. It plays an increasing important role in clinical [[5], [6], [7], [8], [9]].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the use of various types of stents for stula closure have been reported. Most of these studies were comprised of small series with limited evidence, except that Han et al (15) reported the use of a new customized covered metallic stent in a larger study population (n=148). Despite the high success rate, the stents used to be customized from the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…resection, reconstruction) being technically inappropriate or contraindicated; (4) surgical failure or recurrence following surgery. We excluded the patients with the following conditions [15]: (1) hemodynamic instability; (2) severe cardiovascular and cerebrovascular diseases; (3) severe thrombocytopenia and/or severe coagulopathy;…”
Section: Patients and Data Reviewmentioning
confidence: 99%
“…Rigid bronchoscopy is used for diagnostic and therapeutic purposes, in procedures where flexible bronchoscopy would be deemed difficult or even impossible, like obtaining larger samples of endobronchial lesions, foreign body removal, management of central airway obstruction (including ablative techniques, like electrocautery, argon plasma coagulation, laser, cryotherapy, among others, and placement of airway stents) or massive hemoptysis. 36 …”
Section: Recommendations For Bronchoscopymentioning
confidence: 99%